Finding Colon Cancer- and Colorectal Cancer-Related Microbes Based on Microbe–Disease Association Prediction - Chen, Yu; Sun, Hongjian; Sun, Mengzhe; Shi, Changguo; Sun, Hongmei; Shi, Xiaoli; Ji, Binbin; Cui, Jinpeng (Frontiers in Microbiology, 2021)
Microbes are closely associated with the formation and development of diseases. The identification of potential associations between microbes and diseases can boost the understanding of various complex diseases. Wet experiments applied to Microbe-Disease Association (MDA) identification are costly and time-consuming. In this manuscript, we developed a novel computational model, NLLMDA, to find unobserved microbe-disease associations, especially for colon cancer and colorectal carcinoma. NLLMDA integrated negative MDA selection, linear neighborhood similarity, label propagation, information integration and known biological data. The Gaussian association profile similarity of microbes and Gaussian association profiles similarity and symptom similarity of diseases were firstly computed. Linear neighborhood method was then applied to the above computed similarity matrices to obtain more stable performance. Thirdly, negative MDA samples were selected and the label propagation algorithm was used to score for microbe-disease pairs. The final association probabilities can be computed based on the information integration method. NLLMDA was compared with other five classical MDA methods and obtained the highest AUC value of 0.9031 and 0.9335 on cross validations of diseases and microbe-disease pairs. The results suggest that NLLMDA was an effective prediction method. More importantly, we found that acidobacteriaceae may be a close links with colon cancer and tannerella may densely associate with colorectal carcinoma.